PENGEMBANGAN MEDIA PEMBELAJARAN KARTU KUARTET BERBASIS KEARIFAN LOKAL DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SDN 060824 SUTRISNO - Siregar, Rizky Zulayha; Lubis, Nabilah Assyifa; Harahap, Nisa Pratiwi; Khairani, Aska; Rizky, Meitha Ghebrilla; Usman, Khairul; Sugianto, Sugianto (Jurnal Review Pendidikan dan Pengajaran, 2024)
Based on observations made at SDN 060824 Sutrisno, it appears that when teachers try to use a variety of learning media students look inactive, sleepy or bored and instead choose to play alone while learning. Therefore, researchers are interested in making quartet card media that is fun, simple, and meaningful for children's social studies learning in elementary school. Quartet cards are a set of cards in which there is text that explains the picture. Children usually play quartet cards, but the content is only limited to cartoon characters, which may not be useful for them because it only serves to make them happy. This study aims to determine the effectiveness of local wisdom-based quartet card learning media for improving the critical thinking skills of elementary school students. The research method in this study is Research and Development (R & D) with data collection techniques through interviews and observation and documentation. The results showed that the quartet card media can increase students' insight in recognizing culture in Indonesia. This learning media can also foster interest in learning and improve learning outcomes of grade IV students. The “Quite Valid” quartet card media design is used, as evidenced by the results of the value validation carried out by material experts with a percentage value of 79%, validation of the value of media experts with a percentage of 87%, and validation of educator responses that get a value of 89%. As well as student learning outcomes show a value ? 80 with proven values obtained through learning outcomes reaching “Very Good” criteria.